The effect of tennis on male bone mineral density: A meta-analysis - Huang Huiwen; Huang Ju; Fu Dong; Fu Yan; Wang Tao (PLoS ONE, 2025)
Background As an asymmetrical sport, tennis positively influences the increase of bone mineral density (BMD) in adolescents. However, most current studies focus on specific body regions, there is a lack of systematic analysis of the impact of tennis on BMD in various parts of the body. Therefore, this study aims to systematically assess the impact of tennis on BMD in different areas of the body. Objective This study aimed to systematically evaluate the effects of tennis on BMD in males. Methods Comprehensive search was conducted across databases including Web of Science, PubMed, CNKI, and Embase to identify high-quality randomized controlled trials examining the effects of tennis on BMD. The search covered literature from database inception to March 2025. Data were screened, extracted, coded, and statistically analyzed using Review Manager 5.3. Study selection was based on the PICOS criteria: (i) male tennis players compared to non-tennis players of the same age; (ii) tennis intervention group versus groups engaging in other regular physical activities; (iii) outcome indicators included bone mineral content (BMC) and BMD; and (iv) study design included cross-sectional studies, cohort studies, or controlled experiments. Result A total of 10 articles involving 761 male participants aged between 10 and 26 were included in the analysis. Tennis intervention was found to significantly improve bone measures in several areas. Specifically, it led to increases in dominant arm BMC (SMD = 0.57 mg/mm, 95% CI [0.01, 1.13], P = 0.04), lumbar spine BMD (MD = 0.10 g/cm 2 , 95% CI [0.08, 0.11], P < 0.00001), dominant arm and radius BMD (SMD = 1.34 g/cm 2 , 95% CI [0.49, 2.80], P = 0.002), and right femur BMD (MD = 0.10 g/cm 2 , 95% CI [0.02, 0.18], P = 0.02). These differences were statistically significant (P < 0.05). Conversely, tennis had no significant effect on whole-body BMC (MD = 25.51 mg/mm, 95% CI [-38.43, 85.35], P = 0.43), non-dominant arm BMC (SMD = 0.03 mg/mm, 95% CI [-0.31, 0.37], P = 0.88), total body BMD (MD = 0.00 g/cm 2 , 95% CI [-0.01, 0.01], P = 0.97), femoral neck BMD (MD = 0.01 g/cm 2 , 95% CI [-0.00, 0.01], P = 0.30), or left femur BMD (MD = -0.01 g/cm 2 , 95% CI [-0.07, 0.05], P = 0.84). These findings were not statistically significant (P > 0.05). Additionally, subgroup analyses further revealed that tennis training exerted a targeted impact on BMD. Training durations of more than 7 years and at least 15 hours per week significantly improved BMD in the dominant arm and radius. Additionally, significant improvements in the non-dominant arm and radius BMD were observed in participants with over 2 years of training experience. Enhancement of greater trochanter BMD was closely associated with age of training initiation, with significant improvements noted when training began after age 15. In contrast, tennis had minimal influence on femoral neck BMD. Conclusion Tennis effectively enhances BMD in the dominant arm, radius, lumbar spine, greater trochanter, and right lower limb. The effects are asymmetrical, favoring the dominant side. Therefore, to maintain balanced development of BMC and BMD in both limbs, it is recommended to include contralateral (non-dominant side) training during tennis practice. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/identifier : CRD42023486547. Registration date: March 10, 2025.